Benefits of the First Pritikin Outpatient Intensive Cardiac Rehabilitation Program. Issue 6 (23rd November 2022) - Racette, Susan B.; Park, Lauren K.; Rashdi, Serene T.; Montgomery, Kristin; McKenzie, Kristin M.; Deych, Elena; Graham, Christopher; Das, Nikhil; Fogarty, Taylor M.; Van Zandt, Alexandria; Carson, Tessa; Durbin, Dotti; et al.
Abstract : Patients referred to the first-ever Pritikin outpatient intensive cardiac rehabilitation (ICR) program during the first 7 yr (2013-2019) were assessed at baseline and upon program completion. The ICR patients had significant improvements in weight, body mass index, waist circumference, dietary patterns, physical function, and health-related quality of life. Abstract : Purpose: Intensive cardiac rehabilitation (ICR) is a comprehensive, medically supervised exercise treatment program covered by Medicare for patients with approved cardiac diagnoses. The aim of this study was to determine the benefits of the first Pritikin outpatient ICR program. Methods: This retrospective analysis included patients referred to ICR or traditional cardiac rehabilitation (CR) during the first 7 yr (2013-2019) at the first facility to implement Pritikin ICR. Intensive cardiac rehabilitation is composed of 36 education sessions on nutrition, exercise, and a healthy mindset, in addition to 36 monitored exercise sessions that comprise traditional CR. Assessments included anthropometrics (weight, body mass index, and waist circumference), dietary patterns, physical function (6-min walk test, [6MWT] Short Physical Performance Battery [SPPB: balance, 4-m walk, chair rise], handgrip strength), and health-related quality of life (Dartmouth COOP, 36-item Short Form Survey). Baseline and follow-up measures were compared within and between groups. Results: A total of 1963 patients enrolled (1507 ICR, 456 CR, 66.1 ± 11.4 yr, 68% male, 82% overweight or obese); 1141 completed the program (58%). The ICR patients completed 22 exercise and 18 education sessions in 9.6 wk; CR patients completed 19 exercise sessions in 10.3 wk. ICR resulted in improvements ( P < .001 pre vs post) in all anthropometric measures, dietary patterns, 6MWT distance, all SPPB components, grip strength, and health-related quality of life. The improvements in anthropometrics and dietary patterns were greater in ICR than in CR. Conclusions: The Pritikin outpatient ICR program promoted improvements in several cardiovascular health indices. Critical next steps are to assess long-term health outcomes after ICR, including cardiac events and mortality.